2022
DOI: 10.1021/acsestwater.1c00439
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics in the Danube River Basin: A First Comprehensive Screening with a Harmonized Analytical Approach

Abstract: In this study, carried out within the Joint Danube Survey 4, a comprehensive microplastic screening in the water column within a large European river basin from its source to estuary, including major tributaries, was realized. The objective was to develop principles of a systematic and practicable microplastic monitoring strategy using sedimentation boxes for collection of suspended particulate matter followed by its subsequent analysis using thermal extraction desorption-gas chromatography/mass spectrometry. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“… 13 , 16 , 23 25 For instance, natural compounds from coniferous trees could lead to PE overquantifications. 26 Furthermore, in the case of PS, Fischer et al showed possible overdeterminations by phenylalanine from proteins during pyrolysis-GC-MS. 27 Regarding PVC, in the current literature, using pyrolysis or TGA, PVC, benzene, or naphthalene has often been used as a quantifier. 6 , 19 , 25 , 27 However, both pyrolysis products are very unspecific as they can also be generated during the pyrolysis of other synthetic polymers, such as PET or organic substances.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 13 , 16 , 23 25 For instance, natural compounds from coniferous trees could lead to PE overquantifications. 26 Furthermore, in the case of PS, Fischer et al showed possible overdeterminations by phenylalanine from proteins during pyrolysis-GC-MS. 27 Regarding PVC, in the current literature, using pyrolysis or TGA, PVC, benzene, or naphthalene has often been used as a quantifier. 6 , 19 , 25 , 27 However, both pyrolysis products are very unspecific as they can also be generated during the pyrolysis of other synthetic polymers, such as PET or organic substances.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, different optical analytical methods, such as microscopy, Raman spectroscopy, or Fourier transform infrared spectroscopy, have been used for the identification of various types of plastic particles. Also, analytical methods using mass spectrometry in environmental samples have been developed for different polymer types, such as polyethylene (PE), polypropylene (PP), polystyrene (PS), poly­(vinyl chloride) (PVC), poly­(ethylene terephthalate) (PET), polycarbonate (PC), or poly­(methylmethacrylate) (PMMA) as well as their additives. Primarily, pyrolysis or thermogravimetric analysis (TGA) has been coupled with gas chromatograpy/mass spectrometry (GC-MS). However, these thermoanalytical methods are still under development and suffer from matrix interferences and false-positive results. ,, For instance, natural compounds from coniferous trees could lead to PE overquantifications . Furthermore, in the case of PS, Fischer et al showed possible overdeterminations by phenylalanine from proteins during pyrolysis-GC-MS .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GC-MS techniques are sensitive to organic residues in an environmental sample. Hence, sample purification with acids, bases, hydrogen peroxide, or enzymes is necessary (Kittner et al, 2022). DSC might be a promising approach for microplastic determination in environmental samples because organic residues would not influence the analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the exploitation of physical properties of polymers, such as melting and crystallization, can increase analytical robustness. In comparison to pyro/ted-GC-MS methods, extensive sample purification is obsolete for DSC (Kittner et al, 2022). Moreover, an approach to establishing an internal standard was investigated.…”
Section: Introductionmentioning
confidence: 99%